Exploring virtual librarianship: second life library 2.0 - Hedreen, Rebecca; Johnson, Jennifer L; Lundy, Mack A; Burnette, Peg; Perryman, Carol; van den Brekel, Guus; Jacobson, Jj; Gullett, Matt; Czarnecki, Kelly (Internet Reference Services Quarterly, 2008)
In April 2006, Alliance Library System and Online Programming for All Libraries partnered to start the Second Life Library 2.0 in the online world Second Life and in August 2006 purchased an island on the Teen grid of Teen Second Life. Second Life is a virtual world, a descendant of multiplayer online games. Educational institutions have recently been drawn into Second Life's robust economy and vibrant cultural life. The Second Life Library 2.0 works with librarians from around the world and with other educational partners such as TechSoup, WorldBridges, and the New Media Consortium. Second Life Library 2.0 provides traditional library services such as ready reference, book discussions, and search assistance, but, at heart, it explores what it means to be a virtual library in a virtual world.
Keywords: Library 2.0; Online Collaboration; Online Education; Second Life; Virtual Librarians; Virtual Libraries; Virtual Worlds; dept.lib